A sociologia no ensino médio: para além das lutas políticas em (des)favor de sua obrigatoriedade - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This work aims to analyze the teaching of Sociology with an emphasis on the performance of teachers from the state public network of the city of Anápolis-GO in the face of interference suffered by regulation and deregulation provided by public educational policies, and the conception of teaching arising from this context of struggles mandatory in school curricula. Faced with the discontinuity in the pedagogical production around the teaching of Sociology in High School and because it is a recent discipline that lacks articulation among teachers, we pose the following problem: What interests underlie both the defense of regulation and deregulation of Sociology in High School? Based on this, this work investigates, in a methodological course of a qualitative approach, a brief historical outline of Sociology, covering from its emergence as a science to the authors who discuss the teaching of Sociology in high school, with a theoretical basis in Comte (2002), Durkheim (1999, 2004, 2014), Marx (2010, 2011, 2017), Ianni (1989) Fernandes (1954, 1976), Meucci (2000, 2015), Sarandy (2011), Oliveira (2011), Silva (2007, 2010), among others. In addition, an analysis of official national and state high school documents was followed, since Law nº 9.394/96 (LDBEN), National High School Curriculum Guidelines (DCNEM), Opinion CNE/CEB 15/98, Resolution CNE /CEB 03/98, CNE Opinion 38/2006, Law No. 11.684/2008, Reference Curriculum for the State of Goiás, until reaching Law No. 13.415/2017 and Curriculum Document for Goiás High School stage, under the assumption of analyzing what is the genesis of the guidelines that guide the teaching of Sociology and what is the place assigned to Sociology within them. To support the analysis and circumvent the epistemological construction of the work, we sought to understand the sociological practice in schools, a fact that led us to investigate this conjuncture, its agents, and its practices, beyond to documental analysis, from questionnaire applications. Trace the course of sociology's intermittence in basic education allowed us seize the obstacles and challenges for its legitimation and consolidation as field of knowledge, once the search lead us to realization that most sociology´s teachers are not qualified in Social Sciences and occupies this space to complement the workload. In addition, there is low collective participation of professors in relation to the purposes of establishing the regulation and consolidation of Sociology as a mandatory subject. In addition, in a national context, the reform of high school is currently the new threat to the teaching of Sociology, since the new high school seeks to promote neoliberal and business values, replacing social life projects of individual life.
Sociology in high school: in addition to political struggles in (dis)favor of its mandatory
Keywords: Ensino de Sociologia; Intermitência da Sociologia; Práxis; Teaching Sociology; Intermittence of Sociology; Praxis; CIENCIAS HUMANAS::SOCIOLOGIA